Scenario Planning in Anticipating the Death of Leaders of The Islamic State of Iraq and Syria (ISIS) Leader to Mitigate Terrorist Attacks in Indonesia (Case Study: The Death of Abu Bakr Al-Baghdadi) - Manik, Sri Helena Patricia; Riyanta, Stanislaus (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
The death of a leader in the Islamic State of Iraq and Syria (ISIS) organization is often followed by calls for revenge, typically initiated with the renewal of bai’at (pledge of allegiance) against those deemed responsible. ISIS tends to incorporate retaliation as part of its response to various global situations perceived as threats to Muslims. This study aims to elaborate on scenario planning in addressing the aftermath of an ISIS leader's death, to mitigate terrorist attacks in Indonesia. The research employs a descriptive qualitative method using scenario planning analysis based on the framework of Scenario Planning by Brands, Christian, Torsten Wulf, and Philip Meissner. These findings must be implemented in a coordinated and sustainable manner to ensure the effectiveness of anticipating and addressing threats from ISIS networks in Indonesia.